Approximate stress analysis of multistringer beams with shear deformation of the flanges - Kuhn, Paul (Report (United States. National Advisory Committee for Aeronautics) ;, 1938)
The problem of the skin-stringer combinations used as axially loaded panels or as covers for box beams is considered from the point of view of the practical stress analyst. By a simple substitution the problem is reduced to the problem of the single-stringer structure, which has been treated in NACA Report no. 608. The method of making this substitution is essentially empirical; in order to justify it, comparisons are shown between calculations and strain-gage tests of three beams tested by the author and of one compression panel and three beams tested and reported elsewhere. --